Inflammation, Insulin Resistance and the Pathophysiology of Depression: Implications for Novel Antidepressant Developments - (:unkn) unknown (AVES, 2020)
This review summarises the impact of chronic low grade inflammation as a causative factor in the pathophysiology of major depression. Evidence is presented to show that proinflammatory cytokines both directly, and indirectly by increasing hypercortisolaemia, desensitise insulin receptors and thereby decrease the transport of glucose into the brain (the diabetic brain). In addition, the proinflammatory cytokines activate the tryptophan-kynurenine pathway which results in the synthesis of the NMDA-glutamate receptor agonist quinolinic acid. This acts as a neurotoxin and facilitates neuronal apoptosis. As metabolic changes initiated by low grade inflammation underlie the pathophysiology of depression, drugs which attenuate the inflammatory cascade may present an approach to the novel development of antidepressants. The review concludes with a summary of drugs which might be considered for their novel therapeutic activity. Key points are; i)Chronic low grade inflammation commonly occurs in major depression and contributes to adverse changes in brain energy metabolism by decreasing insulin receptor function and thereby reducing glucose transport into the brain. ii) Low grade inflammation initiates an increase in the tryptophan-kynurenine pathway which enhances the NMDA-glutamate receptor function and thereby increases neuronal apoptosis, iii) As many of the pathophysiological changes in depression result from dysfunctional brain metabolism caused by chronic low grade inflammation, it is concluded that drugs targeting the inflammatory pathways may offer new possibilities for the development of novel antidepressants.
Keywords: inflammation; insulin resistance; depression; GROWTH-FACTOR EXPRESSION; DOUBLE-BLIND; ALZHEIMERS-DISEASE; FATTY-ACIDS; ETHYL-EICOSAPENTAENOATE; THERAPEUTIC APPROACH; ADJUNCTIVE THERAPY; INTRANASAL INSULIN; MAJOR DEPRESSION; BIPOLAR DISORDER